Effect of Plant Pigments on Broodstock, Egg Quality and Growth of Rainbow Trout - Mehrabi, Yadollah (2006)
Four experiments were conducted to determine the effects of plant pigments (carotenoids) on rainbow trout (Oncorhynchus mykiss) broodstock, egg quality, growth, FCR, SGR, survival and carotenoids retention in the flesh, skin, egg of female and male broodstocks. Six experimental diets with different sources of plant pigments containing alfalfa, clover, carrot, tomato, acorn fruit and corn gluten meal and two other diets consisting of commercial feed + 50ppm artificial astaxanthin for broodstock and commercial feed +100ppm for fingerling and juvenile were examined. In the first experiment the effects of plant pigments on broodstock were studied. In this experiment, each replication contained 10 females and 5 males broodstock aged about four years old with 1240 + 10g lives weight. There were 8 treatments namely control (A) which contained commercial feed and treatment B (A+5%alfalfa meal), treatment C (A+5% clover meal), treatment D (A+5% carrot meal), treatment E (A+5% acorn fruit meal), treatment F (A+5% tomato meal), treatment G (A+5% corn gluten) and treatment H (A+50ppm artificial astaxanthin) for broodstock and (A+100ppm astaxanthin) for fingerling. Duration of this experiment was six months. Results indicated that higher amount of carotenoids deposited in female broodstock as compared to the male broodstock. The amount of different carotenoids deposited in their tissues also varies. For example, females fed with diet H (artificial astaxanthin) retained astaxanthin 32.87 mg/kg and 25.57mg/kg of canthaxanthin in their flesh, while fish fed diet B (alfalfa meal) retained 43.15mg/kg -carotene and 38.2mg/kg -carotene in their flesh. Lycopene was retained the most in fish fed diet F (41.75mg/kg). The female broodstock also retained higher amount of carotenoids in eggs and skin and significantly (P<0.05) different than the control treatment. Similarly, the same results were observed in the flesh, skin and testis of the male broodstocks. Plant pigments had no adverse effect on mortality of broodstock and is significantly different (P<0.05) with the control treatment. Plant pigments also had no negative effect on all stripped fish, but instead they increased the relative fecundity and production of green egg. Fish fed diet F (tomatoes) had the highest relative fecundity of 451.4g/fish and 45991 green egg were produced while the control treatment had only a fecundity of 332.7g/fish and 28997 of green eggs produced and was significantly different (P<0.05) with other treatments. It was shown that plant pigments also increased egg fertilization, survival and reduced mortality in different stages of egg development. Similarly fish fed diet containing tomatoes had the highest fertilized and eyed eggs and hatched into larvae. Plant pigments increased the survival of fish fingerlings that similarly pigments were deposited in the flesh of the fingerlings. Fish fed diet containing artificial astaxanthin had 93.6% survival compared to control and other treatments and was significantly different (P<0.05). Similar results in juvenile were also observed, which showed that plant pigments would increase survival and retention of carotenoids in their flesh. The juvenile fed diet containing tomato had the highest total length (24.2 cm), survival (92.3%), SGR (1.7) and FCR (1.1) and were significantly different (P<0.05) to control. It can be concluded that plant pigments have significant positive effects on health, survival, FCR, SGR, development of egg, and pigment retention in the flesh, skin and gonads. Additionally, carotenoids were shown to protect the fishes against most diseases because they have important roles in respiration, membrane permeability, light absorption and immune system.